A escrita idiomática para tuba nos dobrados seresteiro, saudades e pretensioso de João Cavalcante - Renato Rodrigues Lisboa (2005)
Since its appearance in the 19th century in Brazil, the retreta band (which shares some features with the symphonic band and marching band), has provided services and entertainment on important social dates to the musical life of most of the countrys small cities. It also provides musicians for most Brazilian military bands and the wind sections of symphony orchestras. Its favorite and the most characteristic musical genre is the dobrado, which origins can be traced back to the European military music. Dobrados are usually in a 2/4 meter and formally organized in 3 main sections. In traditional dobrado writing, the tuba plays simple accompaniments, usually the bass notes of the chords in simple rhythms, emphasizing the pulses or the strong parts of the beat. Composer and conductor João Cavalcante (1902 1985), born in the State of Minas Gerais, the Brazilian state with the greatest number of retreta bands (FUNARTE, 2004; SECRETARIA DE ESTADO DA CULTURA DE MINAS GERAIS, 2004), developed a retreta band writing style in which he mixed popular and classical elements. In Seresteiro, Saudades and Pretensioso, three out of his 23 dobrados Cavalcante used unexpected harmonic schemes, symphonic traits (instrumentation, textures and counterpoint), in which the tuba receives a soloistic treatment and plays a central role. This study aims at identifying João Cavalcante´s musical style in these three retreta band dobrados, his idiomatic writing for the tuba and also presenting a catalogue of João Cavalcante´s dobrados.